Thermal ablation in the management of oligometastatic colorectal cancer. (31st December 2022) - De Baere, Thierry; Tselikas, Lambros; Delpla, Alexandre; Roux, Charles; Varin, Eloi; Kobe, Adrian; Yevich, Steven; Deschamps, Frederic
Abstract: Purpose: To review available evidence on thermal ablation of oligometastatic colorectal cancer. Methods: Technical and cancer specific considerations for percutaneous image-guided thermal ablation of oligometastatic colorectal metastases in the liver and lung were reviewed. Ablation outcomes are compared to surgical and radiation therapy literature. Results: The application of thermal ablation varies widely based on tumor burden, technical expertise, and local cancer triage algorithms. Ablation can be performed in combination or in lieu of other cancer treatments. For surgically non-resectable liver metastases, a randomized trial has demonstrated the superiority of thermal ablation combined with chemotherapy compared to systemic chemotherapy alone in term of progression-free survival and overall survival (OS), with 5-, and 8-year OS of 43.1% and 35.9% in the combined arm vs. 30.3% and 8.9% in the chemotherapy alone arm. As ablation techniques and technology improve, the role of percutaneous thermal ablation may expand even into surgically resectable disease. Many of the prognostic factors for better OS after local treatment of lung metastases are the same for surgery and thermal ablation, including size and number of metastases, disease-free interval, complete resection/ablation, negative carcinoembryonic antigen, neoadjuvant chemotherapy, and controlled extra-pulmonary metastases. When matched for these factors, thermal ablation for lung and liver metastases appears to provide equivalent overall survival as surgery, in the range of 50% at 5 years. Thermal ablation has limitations that should be respected to optimize patient outcomes and minimize complications including targets that are well-visualized by image guidance, measure <3cm in diameter, and be located at least 3mm distance from prominent vasculature or major bronchi. Conclusions: The routine incorporation of image-guided thermal ablation into the therapeutic armamentarium for the treatment of oligometastatic colorectal cancer can provide long survival and even cure.